2020
DOI: 10.3897/phytokeys.157.33625
|View full text |Cite
|
Sign up to set email alerts
|

Petrocosmea nanchuanensis (Gesneriaceae), a new species from Chongqing, China

Abstract: A new species, Petrocosmea nanchuanensis Z.Y. Liu, Z.Y. Li & Z.J. Qiu from Mt. Jinfo at Banhe valley of Nanchuan District in Chongqing Municipality (China) is described and illustrated for the first time. Even though this new species is similar to Petrocosmea barbata, it has several significant morphological differences, which includes smaller leaves, repand leaf margin, densely appressed longer pubescences on both surfaces of leaves, larger flower with length of its lower lips about three times longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…All morphological characteristics were observed under a dissecting microscope (Olympus SZ61, Tokyo, Japan), and descriptions were made following the terminology used in Wang et al (1998) . The relevant literature was consulted, including Xu et al (2011) , Qiu et al (2012) , Zhang et al (2013) , Han et al (2018) , Wen (2019) , Jiang et al (2020) , Qiu et al (2020) , Huang and Xin (2021) , in addition to those mentioned in the introduction. The images of type specimens available in virtual herbaria and databases, including RBGE ( https://data.rbge.org.uk/search/herbarium/ ), Kew Herbarium Catalogue ( http://apps.kew.org/herbcat/navigator.do ), MNHN ( https://www.mnhn.fr/en ), PE ( https://pe.ibcas.ac.cn/index.html ), and iPlant ( http://www.iplant.cn/ ) were also examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All morphological characteristics were observed under a dissecting microscope (Olympus SZ61, Tokyo, Japan), and descriptions were made following the terminology used in Wang et al (1998) . The relevant literature was consulted, including Xu et al (2011) , Qiu et al (2012) , Zhang et al (2013) , Han et al (2018) , Wen (2019) , Jiang et al (2020) , Qiu et al (2020) , Huang and Xin (2021) , in addition to those mentioned in the introduction. The images of type specimens available in virtual herbaria and databases, including RBGE ( https://data.rbge.org.uk/search/herbarium/ ), Kew Herbarium Catalogue ( http://apps.kew.org/herbcat/navigator.do ), MNHN ( https://www.mnhn.fr/en ), PE ( https://pe.ibcas.ac.cn/index.html ), and iPlant ( http://www.iplant.cn/ ) were also examined.…”
Section: Methodsmentioning
confidence: 99%
“… Deinanthera W.T. Wang ( Qiu and Liu 2015 ; Qiu et al 2015 ). Presently, the genus comprises 56 species with three varieties ( GRC 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through literature research and studies in the lab and herbaria, we determined that P. parryorum is indeed distributed in China, but so is an undescribed species similar to P. parryorum which we here describe as P. purpureomaculata . Furthermore, the material identified by Qiu (Qiu and Liu 2015) as P. coerulea C.Y. Wu ex W.T.…”
Section: Introductionmentioning
confidence: 99%
“…In April 2017, during a botanical expedition in SE Yunnan Province, near Vietnam's border, we collected some specimens and living plants bearing buds of an unknown species of Petrocosmea . Later, when they flowered in our greenhouse, we compared the plants with all recognized species of the genus in the relevant literature (Wang 1984, 1985, Wang and Pan 1998, Burtt 1998, Wang et al 1998, Li and Wang 2005, Wei and Wen 2009, Gou et al 2010, Middleton and Triboun 2010, Wei et al 2010, Zhao and Shui 2010, Qiu et al 2011, 2012, 2015, Shaw 2011, 2019, Xu et al 2011, Wang et al 2011, Zhang et al 2013, Qiu and Liu 2015, Han et al 2017, 2018a, 2018b, Li et al 2019, Wen 2019, Yang et al 2019) and against specimens of this genus in major herbaria: E, HITBC, IBK, IBSC, K, KUN, MO, NY, PE, US. We found that our newly collected specimen can be distinguished from most other species of Petrocosmea .…”
Section: Introductionmentioning
confidence: 99%